Microenvironmental Alterations in Carbon Nanotube-Induced Lung Inflammation and Fibrosis - Dong, Jie (Frontiers in Cell and Developmental Biology, 2020)
Carbon nanotube (CNT)-induced pulmonary inflammation and fibrosis have been intensively observed and characterized in numerous animal studies in the past decade. Remarkably, CNT-induced fibrotic lesions highly resemble some human fibrotic lung diseases, such as idiopathic pulmonary fibrosis (IPF) and pneumoconiosis, regarding disease development and pathological features. This notion leads to a serious concern over the health impact of CNTs in exposed human populations, considering the rapidly expanding production of CNT materials for diverse industrial and commercial applications, and meanwhile provides the rationale for exploring CNT-induced pathologic effects in the lung. Accumulating mechanistic understanding of CNT lung pathology at the systemic, cellular, and molecular levels has demonstrated the potential of using CNT-exposed animals as a new disease model for the studies on inflammation, fibrosis, and the interactions between these two disease states. Tissue microenvironment plays critical roles in maintaining homeostasis and physiological functions of organ systems. When aberrant microenvironment forms under intrinsic or extrinsic stimulation, tissue abnormality, organ dysfunction, and pathological outcomes are induced, resulting in disease development. In this article, the cellular and molecular alterations that are induced in tissue microenvironment and implicated in the initiation and progression of inflammation and fibrosis in CNT-exposed lungs, including effector cells, soluble mediators, and functional events exemplified by cell differentiation and extracellular matrix (ECM) modification, are summarized and discussed. This analysis would provide new insights into the mechanistic understanding of lung inflammation and fibrosis induced by CNTs, as well as the development of CNT-exposed animals as a new model for human lung diseases.